Abiotrophia defectiva causing infective endocarditis with brain infarction and subarachnoid hemorrhage: a case report - Yang, Miaojuan; Lin, Yanxia; Peng, Xin; Wu, Jingsong; Hu, Bo; He, Yitao; Lu, Jian (Frontiers in Medicine, 2023)
Introduction A rare pathogen of Infective Endocarditis (IE), the Abiotrophia defectiva, has been known to trigger life-threatening complications. The case discussed here is of a teenager with brain infarction and subarachnoid haemorrhage caused by IE due to A. defectiva. Case Report A 15-year-old girl with movement disorders involving the left limbs and intermittent fevers was admitted to the hospital. A head CT scan revealed cerebral infarction in the right basal ganglia and subarachnoid haemorrhage. Moreover, vegetation on the mitral valve were confirmed by echocardiography. The blood cultures were found to be positive for Gram-positive streptococcus and identified by Vitek mass spectrometry as A. defectiva. She was prescribed vancomycin antibacterial therapy and underwent a surgical mitral valve replacement. Conclusion This case is suggestive of the fact that A. defectiva is a rare but crucial pathogen of IE-associated stroke. Obtaining early blood cultures and using microbial mass spectrometry could help achieve an accurate diagnosis. Moreover, reasonable anti-infective medications and surgical interventions need to be combined to avoid and/or manage severe complications.